Analisa Dampak Lalulintas Hotel Diamond Manado - Butar-butar, Samuel H. H.; Rompis, Semuel Y. R.; Timboeleng, James A. (Sam Ratulangi University, 2017)
Along with the development of a city and the increasing flow of traffic, the growth of urban hospitality is also increasing.The hotel not only serves as a stopover or temporary accommodation but in its development the function of hospitality also as a place of social interaction, education, culture and religious. The construction of the Diamond Hotel on Sam Ratulangi road has a positive impact on improving the economy by becoming one of the sources of local revenue (PAD). The smoothness of hotel activities in the form of place to stay and other activities and pressing the unemployment rate with the absorption of labor so that it can become an icon of progress of a region, but in addition to positive impact of the construction of this hotel is also expected to impact on the environment one of which is the impact of traffic. This development plan will create new problems and add to the complexity of traffic aspect. As a source of new traffic generated accessible to the public, its presence will provide additional traffic volume.Therefore, it is necessary to analyze the impact of traffic, so that the existence of the hotel does not negatively affect the traffic (road users), not only for Diamond Hotel but also the general public, both those concerned with the hotel and the passing road users.The aims of this study is to predict the attraction of traffic movement due to the Diamond Manado hotel and its impact on Sam Ratulangi road performance.Method of study consists of: Initial Site Survey (Determination of Observation Post),(2) Determination of Survey Period and equipment in use: (a). Primary data collection Survey of traffic volume, Speed, existing attraction and and any attraction at similar hotels, (b). Secondary data collection Network road and land use, Lay out of Hotel Diamond and (c). Data Processing: attraction analysis and traffic volume using attraction analysis in similar hotels, Performance Analysis of Sam Ratulangi Road ahead of WP using Traffic Flow Model and MKJI, Forecasting the amount of attraction in the future. Based on the results of the analysis discussed earlier, it can be concluded as follows: 1.The attraction of visitors due to the activity of Diamond Manado Hotel resulted in an increase in traffic that made the reduce in the capacity of Sam Ratulangi manado road. 2. The performance of Sam Ratulangi road segment after the attraction of movement from Hotel Diamond Manado could be determine by its level of service (LoS). 3. By knowing the prediction of the attraction of movement, it is necessary to anticipate the step to overcome the increase in the amount of movement to the Manado Diamond Hotel, such as the optimization of parking lots, and more regular parking management.Keywords: traffic impact, urban hospitality, sources of local revenue, attraction of traffic, parking management